Republic of Burundi Skills Development for Growth : Building Skills for Coffee and Other Priority Sectors - World Bank (Washington, DC, 2014)
With limited land, capital, and a fast growing population, Burundi's main asset is its youthful population. Its main challenge is also to create good quality jobs for its youth. With low levels of educational attainment and poor health status, the quality of this young population is poor. After more than 13 years of conflict ending in 2000, and a period of modest recovery, Burundi has the opportunity to stimulate growth. Burundi is making strides in creating one of the fundamentals of job creation - investment climate. Investing in the skills of the population is critical for the success of growth strategy and for creating productive employment opportunities for Burundi's youth. The Government of Burundi is introducing a major reform in the education sector which is going to significantly impact skills in Burundi. This analytical report will contribute to defining a skills development strategy for Burundi to complement the growth strategy. It looks at the potential impact of the basic education reform on the quantity and education attainment of the working age population. Further it looks at the skills demands that are likely to emerge if Burundi upgrades along the value chain in selected sectors to ensure strong alignment of occupation competencies in growth sectors. The report is structured as follows: section one gives introduction. Section two gives impacts of the new basic education reform, and its pace of implementation, for the education levels of potential new workers, and of the population, over the next 10-15 years. Section three presents the potential upgrading strategies for moving up the value chain in the selected sectors. Section four presents current framework for strategic direction, demand-led approach, and coordination of the technical vocational education and training (TVET) system.